2013
DOI: 10.5539/ijps.v5n1p91
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Communication and Conflict Resolution Skills Training on Mental Health

Abstract: This study examined the effects of communication and conflict resolution skills training on mental health among
Iranian couples based on the PREPARE/ENRICH program. In this study, mental health was measured by
General Health Questionnaires (GHQ28). The study adopted a pre- and post-control group design in
emphasizing the effects of communication training and conflict resolution skills on mental health. The
participants in this research consisted of couples who were referred to the researche…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 47 publications
(39 reference statements)
1
10
0
1
Order By: Relevance
“…The present study indicated that the efforts made to increase women's communication skills would be associated with their improved psychological health and increased marital satisfaction. Many studies have shown that communication skill training is effective in reducing marital conflicts [19,20] and improving the communication between couples [16], and improves the couples' psychological health [13,21]. During pregnancy, due to physical and emotional changes in women, abnormal relationships may be experienced by the couples [2]; however, this study confirmed that during pregnancy, like other periods of life, communication skills training for women can improve such communications and relationships.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The present study indicated that the efforts made to increase women's communication skills would be associated with their improved psychological health and increased marital satisfaction. Many studies have shown that communication skill training is effective in reducing marital conflicts [19,20] and improving the communication between couples [16], and improves the couples' psychological health [13,21]. During pregnancy, due to physical and emotional changes in women, abnormal relationships may be experienced by the couples [2]; however, this study confirmed that during pregnancy, like other periods of life, communication skills training for women can improve such communications and relationships.…”
Section: Discussionsupporting
confidence: 62%
“…In order to maintain and improve the mental health of pregnant women, we need to increase the ability of couples to resolve their conflicts, after formation of new relationships between partners due to the physical and emotional changes during pregnancy. Evidence suggests that acquiring communication skills can improve the quality of marital relationships and reduce psychological disorders such as depression and anxiety [13].…”
Section: Introductionmentioning
confidence: 99%
“…El interés en explicar la satisfacción y la estabilidad en la trayectoria de las relaciones interpersonales ha sido punto central en diferentes estudios de parejas (Schoebi, Karney, y Bradbury, 2012); a la vez, estudios previos han demostrado la eficacia de las intervenciones, a través de programas de entrenamiento de desarrollo de habilidades de resolución de problemas, para reducir los conflictos y aumentar la satisfacción en las relaciones interpersonales de los jóvenes (por ejemplo, Askari, Mohd, Aishah, y Baba, 2013;Perrone-McGovern et al, 2014;Robertson, Fish, Olmstead, y Fincham, 2015). Se ha constatado, incluso, que es posible la mejora de las estrategias de afrontamiento en agresores de género a partir de un entrenamiento reeducativo específico (Arce, Fariña, y Novo, 2014).…”
unclassified
“…There is a positive association between the quality of co-parenting and the marital relationship (Morrill et al, 2010). Regarding the co-parenting alliance, the positive marital communication and effective ability to resolve conflicts seem to improve the couple's relationship (Askari et al, 2013). Communication is significantly related to couple satisfaction and the ability to resolve conflicts/misunderstandings (Carrère & Gottman, 1999;Litzinger & Gordon, 2005).…”
Section: Parenting Correlatesmentioning
confidence: 98%